Retropharyngeal abscess causing grisel’s syndrome secondary to tuberculosis of cervical spine, a rare form of torticollis: case report - Sivarajan, Reegina; Mahfuz, Mohammad Fuaz; Sanudin, Siti Hajar (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2021)
Grisel’s syndrome is a rare type of non-traumatic subluxation of an atlantoaxial joint characterized by torticollis, neck pain, and reduced neck movement. The common causes of Grisel’s syndrome are head and neck infection or post-otorhinolaryngology (ORL) procedures. We are reporting a case of a 3-year-old boy with a gradual worsening of neck stiffness, neck pain, and restricted neck movement for more than one month. The patient had no history of trauma. The computerized tomographic (CT) showed a retropharyngeal abscess with a bony erosion causing atlantoaxial subluxation. The management and progress of this patient are discussed. The objective of this case report is to emphasize that Grisel’s syndrome should be considered a differential in a painful torticollis to prompt an early diagnosis and treatment to prevent serious neurological complications.